TANTANGAN BELAJAR MATEMATIKA DALAM MATERI ARITMATIKA SOSIAL PADA PESERTA DIDIK BERKEBUTUHAN KHUSUS - Adinda Cintya Wulandari; Sugiatno Sugiatno; Bistari Bistari (UNIVERSITAS TANJUNGPURA, 2020)
Advantages in mathematics education require high equality and strong support for all students and students from different backgrounds both social life and those in remote areas need to get equality in mathematics education. Learning challenges are basically caused by the emergence of students' obstacles in learning that students feel in the process of teaching and learning mathematics so that students are slow or unable to achieve their learning goals properly. In order to be able to spur the success of the mathematics learning process for SLB students, therefore we need basic facilities and infrastructure or supporting student success. The research aims to explore the cognitive factors that cause the challenges of learning mathematics in social arithmetic material in students with special needs. Descriptive method is used in this research. in the research subject consisted of 4 students of class VIII Extraordinary Middle School - B Dharma Asih Pontianak. The data obtained include student learning outcomes in social arithmetic material and student interviews. The results showed that 75% have not been able to work on social arithmetic problems so that the cognitive factors that cause the more dominant mathematical learning challenges affecting the four subjects are understanding and application.Keywords: Children with Special Needs, Learning Challenges, Social Arithmetic